1996
DOI: 10.3109/10611869609046269
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetic, immunologic and hematologic studies on the anti-HIV-1/2 compounds aconitylated and succinylated HSA

Abstract: Charge modification by succinylation or cis-aconitylation of the terminal epsilon NH2 functions of the amino acid lysine in human serum albumin, resulted in polyanionic compounds with an anti-HIV-1 activity in the low nanomolar concentration range. After iv injections in rats of the negatively charged albumins (NCAs), a dose dependent elimination pattern was observed indicating a saturable eliminations pathway. The Michaelis-Menten parameters Vmax and K(m) were 62 +/- 8 micrograms.min-1.kg-1 and 16 +/- 4 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Since the primary interaction appears to be dependent on charge density rather than a particular structural motif (57), it seems unlikely that the specificity essential for effective therapeutic treatment is present. This does not bode well for drug development based on polyanions such as sulfated polysaccharides (2,24,35), carboxylated albumins (26,51), porphyrins (13,49), or DNA or RNA derivatives (31). Nevertheless, the unusual basicity observed for the CXCR4-using viruses may, in this particular case, permit anion-based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Since the primary interaction appears to be dependent on charge density rather than a particular structural motif (57), it seems unlikely that the specificity essential for effective therapeutic treatment is present. This does not bode well for drug development based on polyanions such as sulfated polysaccharides (2,24,35), carboxylated albumins (26,51), porphyrins (13,49), or DNA or RNA derivatives (31). Nevertheless, the unusual basicity observed for the CXCR4-using viruses may, in this particular case, permit anion-based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Other labeling techniques such as fluorophores or direct coupling of the radio isotope 125 I have been used for labeling siRNAs. However, these labeling approaches may influence the pharmacokinetics and pharmacodynamics, as highlighted already for modified proteins (Swart et al …”
Section: Introductionmentioning
confidence: 99%
“…Overall, drug candidates with attached pendant groups containing complexed isotopes are often assumed to not alter the reactivity or metabolism of the molecules. However, this labeling approach has previously been shown to influence the pharmacodynamic and pharmacokinetic behavior of large molecules, such as for proteins by Swart et al (1996). ABBREVIATIONS: ADME, absorption, distribution, metabolism, and excretion; ESI, electrospray ionization; HPLC, high-performance liquid chromatography; MRP4, multidrug resistance protein isoform 4; MS, mass spectrometry; QWBA, quantitative whole-body autoradiography; siRNA, short interfering RNA; SSB, Sjögren Syndrome antigen B; UHPLC, ultra high-performance liquid chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using proteins have shown that labeling by 125 I affected the pharmacokinetics, compared with the molecule labeled with carbon-14 (Swart et al, 1996).…”
mentioning
confidence: 99%